Achieving the millennium development goals : strategies from Fazle H. Abed, founder and chairperson of BRAC - Abed, Fazle; Global academy for Entrepreneurship/ SKOLL Foundation (ASHOKA (Innovators for the Public).)
Abed in this video discusses his efforts and astounding success thus far and addresses trade issues and the importance of strong democray.
DVD.
Keywords: Economic assistance -- International corporation -- Developing countries; Poverty Developing countries; UN millennium project